2018
DOI: 10.1186/s13148-018-0550-8
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of MAGE family in human cancer progression-DNA methylation, histone modification, and non-coding RNAs

Abstract: The melanoma antigen gene (MAGE) proteins are a group of highly conserved family members that contain a common MAGE homology domain. Type I MAGEs are relevant cancer-testis antigens (CTAs), and originally considered as attractive targets for cancer immunotherapy due to their typically high expression in tumor tissues but restricted expression in normal adult tissues. Here, we reviewed the recent discoveries and ideas that illustrate the biological functions of MAGE family in cancer progression. Furthermore, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 91 publications
1
49
0
1
Order By: Relevance
“…In cancer cells, MAGE-A members show abnormal expression, leading to the acquisition of tumor-promoting properties such as tumor growth, proliferation, migration, and invasion with concomitant inhibition to apoptosis [5]. The abnormal activation of MAGE family genes is now attributed to epigenetic dysregulation such as DNA hypomethylation, defective histone modifications, and nucleosome occupancy [16]. DNA hypomethylation has been shown to induce aberrant expression of MAGE-A genes and is associated with poor survival outcomes in laryngeal squamous cell carcinoma and esophageal squamous cell carcinoma [87,88].…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cells, MAGE-A members show abnormal expression, leading to the acquisition of tumor-promoting properties such as tumor growth, proliferation, migration, and invasion with concomitant inhibition to apoptosis [5]. The abnormal activation of MAGE family genes is now attributed to epigenetic dysregulation such as DNA hypomethylation, defective histone modifications, and nucleosome occupancy [16]. DNA hypomethylation has been shown to induce aberrant expression of MAGE-A genes and is associated with poor survival outcomes in laryngeal squamous cell carcinoma and esophageal squamous cell carcinoma [87,88].…”
Section: Discussionmentioning
confidence: 99%
“…The panel included 10 target genes (TERT, ZAP70, GP1BB, LRRTM1, FLI1, MiR124-1, MiR296, KIF1A, PARP15 and MAGEC2), selected because their human orthologs were previously identified with altered methylation pattern in human head and neck squamous cell carcinoma (SCC). 17,22,25,[32][33][34][35][36] In order to identify putative CpG islands on promoter region of genes or in the first part of the coding region, genomic sequence stored on the Ensembl genome browser (http://www.ensembl.org/index.html) were employed as query sequence, considering the best homology of each feline gene region with human orthologues. the MethPrimer (http://www.urogene.org/cgi-bin/methprimer/methprimer.cgi) designing was applied to identify CpGs and the best primers of choice.…”
Section: Dna Methylation Analysismentioning
confidence: 99%
“…It is important to understand how germline genes are repressed in somatic tissue as many human somatic cancers that are highly proliferative and metastatic show upregulation of germline genes (Gure et al, 2005;Maine et al, 2016;Xu et al, 2014). Like C. elegans, mammals also repress germline gene expression during embryogenesis in somatic cells and recent work has indicated that this repression is dependent on H3K9me2 (Ebata et al, 2017;Lian et al, 2018). Given that the DREAM complex is completely conserved between worms and mammals (Litovchick, et al, 2007), its role in establishment of developmental repressive chromatin at germline genes may also be conserved.…”
Section: Discussionmentioning
confidence: 99%